Research into the influence of climatic factors on the losses of electric energy in overhead power transmission lines - Bakulevskiy, Vladimir (Eastern-European Journal of Enterprise Technologies, 2016)
The problem of improving the accuracy in the calculations of technical energy losses in the overhead transmission lines of voltage 6–35 kV was examined by taking into account climatic factors. The influence of climatic factors on the losses of electricity in the overhead transmission lines of voltage 6–35 kV was explored. We improved the model of thermal processes in the PTL wires through a fuller account of meteofactors. The approaches to calculating the losses of active power in PTL were analyzed and examined. We substantiated expediency of applying the approach in which the losses are calculated taking into account the average monthly air temperature. It was investigated, calculated and proposed to include, in the basic equation of thermal balance for the PTL wires, the heat transfer coefficients that take into account the impact of precipitation (rain, snow). We improved the basic equation of thermal balance for sustained thermal mode for the PTL wires with regard to the proposed approach to the selection of temperature and calculated heat transfer coefficients at atmospheric precipitation on the surface of the wires. The expression is proposed for determining technical energy losses in the overhead PTL of voltage 6–35 kV. We designed a model of neural network for forecasting and calculating technical energy losses in the overhead power transmission lines of voltage 6–35 kV, which has advantages in comparison with traditional models and will make it possible to reduce error when calculating and forecasting load electric power losses in PTL. Results of the study may be useful for forecasting and calculation of energy losses in the overhead PTL of voltage 6–35 kV in power supply and designing organizations.